Pertanggungjawaban Badan Hukum dalam Tindakan Melawan Hukum: Studi Kasus dalam Gugatan Ganti Rugi - Ida Bagus Bayu Brahmantya (Syntax Idea)
A legal entity is an organization that has legal rights and obligations. Legal actions taken by legal entities can cause harm to other parties. Parties harmed by legal acts committed by legal entities may file a lawsuit for compensation against the legal entity. The purpose of this research is to analyze the liability of legal entities in tort actions with a case study in a lawsuit for compensation. The research method used in this research is normative legal research method. The data collection technique in this research is a document study obtained from Google Schoolar. The data analysis technique used in this research is qualitative analysis technique. The results of this research show that legal entities can be held liable for their unlawful acts. Legal entities can be held civilly and criminally liable. Civil liability of legal entities is the obligation of legal entities to compensate for losses suffered by the injured party. Criminal liability of a legal entity is the obligation of a legal entity to be punished by the state for committing a criminal offense.